2021
DOI: 10.3389/fcell.2021.621645
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for Cell Therapy to Treat Stroke?

Abstract: Clinical trials of cell therapies that target stroke started at the beginning of this century and they have experienced a significant boost in recent years as a result of promising data from basic research studies. The increase in the information available has paved the way to carry out more innovative and varied human studies. Efforts have focused on the search for a safe and effective treatment to stimulate neuro-regeneration in the brain and to reduce the sequelae of stroke in patients. Therefore, this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 68 publications
(109 reference statements)
0
9
0
1
Order By: Relevance
“…Transplantation of mesenchymal stem cells (MSCs) is a novel approach to the treatment of many severe neurological disorders causing irreversible damage of neural tissue, including traumatic brain injury, spinal cord injury, multiple sclerosis, neurodegenerative diseases, and stroke [ 1 , 2 , 3 ]. In the case of stroke, different routes of MSCs administration, including direct intracerebral, intrathecal, intraventricular, intravenous, intra-arterial, intranasal, and others have been tested in animal studies [ 4 , 5 ]. Among them, the intra-arterial (IA) delivery appears one of the most effective, probably because it guarantees targeted cell delivery to the brain vascular system [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplantation of mesenchymal stem cells (MSCs) is a novel approach to the treatment of many severe neurological disorders causing irreversible damage of neural tissue, including traumatic brain injury, spinal cord injury, multiple sclerosis, neurodegenerative diseases, and stroke [ 1 , 2 , 3 ]. In the case of stroke, different routes of MSCs administration, including direct intracerebral, intrathecal, intraventricular, intravenous, intra-arterial, intranasal, and others have been tested in animal studies [ 4 , 5 ]. Among them, the intra-arterial (IA) delivery appears one of the most effective, probably because it guarantees targeted cell delivery to the brain vascular system [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rapid development of the endovascular mechanical thrombectomy technique and its widespread use in acute stroke treatment made IA transplantation more feasible for routine clinical practice [ 9 , 10 ]. According to the ClinicalTrials.gov site, five-phase I and II clinical trials focused on IA administration of MSCs or bone marrow mononuclear cells into patients with subacute or chronic ischemic stroke have been registered throughout the world and some of them have been already completed (reviewed in [ 4 , 11 ]). The published results of the clinical trials indicate that IA transplantation of cells is essentially safe in humans and can promote some neurological improvement after stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation of different types of stem cells has the potential to develop into an effective method of stroke therapy [ 6 , 7 ]. Specifically, over the past two decades, multiple basic studies and clinical trials have demonstrated that transplantation of the mesenchymal stem cells (mesenchymal stromal cells, MSCs) is safe [ 8 ] and can promote recovery after stroke (reviewed in [ 9 , 10 ]). According to the International Society of Cell Therapy criteria, MSCs are defined as multipotent non-hematopoietic stem cells that are adherent to plastic and can differentiate into adipocytes, chondroblasts, osteoblasts, and myocytes in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Several routes of MSC transplantation in stroke, including the intra-arterial (IA), intravenous (IV), intraperitoneal, intracerebral, intraventricular, intrathecal, and intranasal delivery were tried and showed therapeutic efficacy [ 10 , 31 ]. However, the best delivery route, as well as the ‘therapeutic window’ duration have not been so far agreed upon.…”
Section: Introductionmentioning
confidence: 99%